Antiparasitic activity of the iron-containing milk protein lactoferrin and its potential derivatives against human intestinal and blood parasites - Anand, Namrata (Frontiers in Parasitology, 2024)
An iron-containing milk protein named lactoferrin (Lf) has demonstrated antiparasitic and immunomodulatory properties against a variety of human parasites. This protein has shown its capability to bind and transport iron molecules in the vicinity of the host-pathogen environment. The ability of parasites to sequester the iron molecule and to increase their pathogenicity and survival depends upon the availability of iron sources. Lf protein has suggested a possible chelating effect against parasite iron and hence has shown its antiparasitic effect. Since the parasites have complex life cycle and been shown tohave developed drug resistance, vaccines, and other treatments are a handful. Therefore, therapeutic research focusing on natural treatment regimens that target the parasite, and non-and are not toxic to host cells is of utmost need. The antiparasitic efficacy of Lf protein has been extensively studied over the past 40 years using both in vitroinvitro and in vivoinvivo studies. This review article highlighted past important studies on Lf protein that revealed its potential antiparasitic activity against various intracellular and extracellular intestinal or blood-borne human parasites. The review article structures the role of Lf protein in its various forms such as native, peptide, and nanoformulation, laying the groundwork for its function as an antiparasitic agent and its also highlights its possible known mechanisms of action.